Changes in a top-level soccer referee`s training, match activities, and physiology over an 8-year period: A case study - Weston, M.; Gregson, W.; Castagna, C.; Breivik, S.; Impellizzeri, F. M.; Lovel, R. J. (International Journal of Sports Physiology and Performance, 2011)
Athlete case studies have often focused on the training outcome and not the training process. Consequently, there is a dearth of information detailing longitudinal training protocols, yet it is the combined assessment of both outcome and process that enhances the interpretation of physical test data. We were provided with a unique opportunity to assess the training load, physical match performance, and physiological fitness of an elite soccer referee from the referee`s final season before attaining full-time, professional status (2002) until the season when he refereed the 2010 UEFA Champions League and FIFA World Cup finals. An increased focus on on-field speed and gym-based strength training was observed toward the end of the study period and longitudinal match data showed a tendency for decreased total distances but an increased intensity of movements. Laboratory assessments demonstrated that VO2max remained stable (52.3 vs 50.8 mL/kg/min), whereas running speed at the lactate threshold (14.0 vs 12.0 km/h) and running economy (37.3 vs 43.4 mL/kg/min) both improved in 2010 compared with 2002.